TINJAUAN APLIKASI SERAT SABUT KELAPA SEBAGAI PENGUAT MATERIAL KOMPOSIT - Bakri, Bakri (Jurnal MEKANIKAL, 2011)
Natural fibres as reiforcement of composite have been concerning in the last decade. These have changed in use convestional fibre like glass fibre and carbon fibre related to environmental effect. One of natural fibres can potensially change conventional fibre is coir fibre. This fibre is abundant in tropical areas such as India, Brazil and Indonesia. In this paper, an overview of aplication of coir fibre as reinforced composite in some uses was described.